Selection and characterisation of lactic acid bacteria isolated from different origins for ensiling Robinia pseudoacacia and Morus alba L. leaves - Kui-kui NI; Hui-xiao YANG; Wei HUA; Yan-ping WANG; Hui-li PANG (Journal of Integrative Agriculture, 2016)
The objective of this study was to isolate lactic acid bacteria (LAB) strains from different origins and to select the best strains for ensiling Robinia pseudoacacia (RB) and Morus alba L. (MB) leaves. The LAB strains were inoculated into the extracted liquid obtained from RB and MB leaves to evaluate the fermentation products. 11 LAB strains were selected for further experiments based on the highest products of lactic or acetic acid, including 1 strain of Weissella confusa, 2 of Lactobacillus reuteri and 8 of Lactobacillus plantarum. The API 50 CH fermentation experiment indicated that all of the selected 11 LAB strains utilised most of the carbohydrates. All the strains grew at temperatures between 10 and 45°C and at a pH of 3.5 to 4.5; however, L. reuteri F7 and F8 tolerated a pH as low as 3.0. All 11 LAB strains showed antibacterial activity against Listeria monocytogens, Escherichia coil, Salmonella sp. and Acetobacter pasteurianus; however, after excluding the effect of organic acids, only F7 and F8 still exhibited antibacterial activity. The present study indicated that the selected 11 LAB strains could be used to prepare silages of RB and MB leaves, especially L. reuteri F7 and F8.